Adolescent mental health interventions: a narrative review of the positive effects of physical activity and implementation strategies - Li, Zhaojin; Li, Jie; Kong, Jianda; Li, Zhilin; Wang, Rui; Jiang, Fugao (Frontiers in Psychology, 2024)
Introduction: The psychological well-being of adolescents is a global concern due to increasing societal pressures and mental health issues. Physical activity is known to enhance physical health and has potential benefits for mental health, including reducing symptoms of anxiety and depression, boosting self-esteem, and improving social skills. This narrative review explores how physical activity can serve as an intervention to help adolescents manage psychological stress and prevent mental health issues. Methods: An extensive literature search was conducted using databases such as PubMed, PsycINFO, Web of Science, and Scopus. Keywords included "adolescent mental health," "physical activity," "psychological intervention," "types of exercise," "anxiety," "depression," "self-esteem," "social skills," and "emotional regulation." Studies were included based on relevance, peer-reviewed status, and involvement of adolescent populations. Data were extracted and analyzed qualitatively, focusing on the psychological impacts of different types of physical activity. 61 articles were eventually included. Results and Conclusion: The review identified multiple studies highlighting the positive effects of various physical activities on adolescent mental health. Aerobic exercises were found to improve mood and cognitive function, strength training reduced depressive symptoms and increased self-efficacy, team sports enhanced social skills and a sense of community, and mind-body practices like yoga and tai chi improved stress management and emotional regulation.The findings suggest that physical activity can play a significant role in promoting adolescent mental health. Implementation strategies in school and community settings, including integrating physical activity into school curricula, offering diverse activity options, training professional instructors,